NKRA NKPI x NKIP = GTP - Abd Razak, Dzulkifli (2009)
If it is assumed that we want to build a house, the dream is now almost achieved. The house design is clear, dimensions are ready and the framework having been agreed to. Such can be said in building a “new” Malaysia by 2020. Although the 2020 dream clearly reflects our future, the surface of various global crisis, especially economic crisis, it also affects the overall picture for 2020. .In addition with the fear that Malaysian is trapped with mediocre economy, necessary measures have been drafted to ensure Vision 2020 is achieved.